ANALISIS PROFIL ATRIBUT SENSORI BANDENG ASAP PRODUKSI UMKM KABUPATEN SIDOARJO DENGAN METODE RATA (RATE-ALL-THAT-APPLY) - Syari, Ririef Mutiara; Sarofa, Ulya; Pratiwi, Yunita Satya (Universitas Tribhuwana Tunggadewi, 2025)
Smoked milkfish is a processed fish, a signature item of Sidoarjo Regency. Smoked milkfish has different criteria depending on the production process. Sensory attributes are among the most important consumer preferences. This study aimed to examine the sensory attributes of smoked milkfish and determine the dominant sensory attributes that influence consumer preferences. The Rate-All-That Apply (RATA) method was used to determine the tested food products. Five samples of smoked milkfish were tested with 70 respondents residing in Surabaya and Sidoarjo. There are 13 significantly different sensory attributes, including aroma (smoky, sweet), taste (savory, sour, sweet, salty, spicy), color (brown, golden yellow, reddish), and texture (dry, fibrous, wet). The distinguishing parameters of the five samples are their unique characteristics. The results of Principal Component Analysis (PCA) showed that samples 134 and 534 had dominant attributes of sweet taste, salty taste, spicy taste, brown color, sweet aroma, and smokiness. Sample 315 had a fibrous texture and sour taste. Sample 231 had a dominant wet texture and yellow color. Sample 405 had a dominant dry texture, savory taste, and reddish color. The preference mapping showed that the most preferred sample was 134.